Production yearbook : Volume 28 - Food and Agriculture Ortganization of the United Nations; Food and Agriculture Organization of the United Nations (Rome : Food and Agriculture Ortganization of the United Nations, 1974)
This book contains data on prices of agricultural products, prices of productions, freight rates, farm rates and index number of prices.
This book is translated into English and French
Includes bibliographical references
mf 24/01/2019
Loans
Keywords: Agriculture---Economic aspects; Produce trade